Morphogenic parameters and productivity of grass-Pioneer subjected to nitrogen - Lobo, Bernado Silveira; Sales, Eleuza Clarete Junqueira de; Reis, Sidnei Tavares dos; Monção, Flávio Pinto; Pereira, Daniela Alves; Rigueira, João Paulo Sampaio; Oliveira, Polyanna Mara de; Mota, Verônica Aparecida Costa; Alves, Dorismar David (Semina: Ciências Agrárias, 2014)
Objective of this work by evaluating the effect of nitrogen on forage yield and morphogenesis of elephant grass cv. Pioneer. The experimental design was randomized blocks with five replications, totaling 20 experimental units. Treatments consisted of four nitrogen levels (100, 200, 300 and 400 kg ha-1 yr-1). The experiment was conducted under irrigated conditions. Evaluative cuts were made at 50 cm soil with values of light interception (95%) without pre-defined intervals. It was observed that N fertilization increased significantly (P<0.05) the production of dry matter per hectare, leaf appearance rate (leaves days -1tiller-1), leaf elongation rate (cm tiller-1 day-1) and stem elongation rate (cm day-1). The process of this forage senescence is accelerated with increasing doses of nitrogen and leaf appearance rate, thereby reducing the phyllochron. It required a study on the economic viability of higher doses of nitrogen in grazed elephant grass cv. Pioneer.